Usefulness of APACHE-II, SOFA, ISARIC/WHO 4C Mortality Score and CO-RADS for Mortality Prediction of Critically Ill Coronavirus Disease-2019 Patients - Hülya Sungurtekin; Fatih Sargın; Metin Kılınç; Mithat Kahramanoğlu; Mert Akbulut; Ferruh Ayoğlu; Ahmet Çalışkan; Simay Karaduman (Galenos Yayinevi, 2023)
Objective:It was aimed to report the Acute Physiology and Chronic Health Evaluation-II (APACHE-II) score, Sequential Organ Failure Assessment (SOFA) score, Glasgow coma scale (GCS), 4C mortality score and the coronavirus disease-2019 (COVID-19) Reporting and Data System (CO-RADS) in predicting the outcome of critically ill COVID-19 patients.Materials and Methods:Patients with laboratory-confirmed COVID-19 infection or clinical and radiological confirmed COVID-19 infection who were admitted to adult intensive care unit (ICU) were included. Clinical characteristics, outcomes, APACHE-II score, SOFA score, International Severe Acute Respiratory and Emerging Infections Consortium/World Health Organization 4C mortality score and CO-RADS classification were reported at admission.Results:Two hundred seventy six patients were included in this study. The mean age was higher in non-survivor patients. The most common cause of hospitalization was respiratory failure (67%). The common co-morbidities were hypertension (51.8%), cardiac disease (43.4%) and diabetes (33.6%). Organ failure was present in 61.5% of the patients. The mean APACHE-II, SOFA, GCS and 4C mortality scores were higher in non-survivor patients. 4C mortality and SOFA scores showed higher predictive accuracy for mortality with an area under the curve 0.736 and 0.706, respectively. 4C mortality had sensitivity of 78.9% and specificity of 58.1% whereas of SOFA had a sensitivity of 78.9% and a specificity of 53.3%.Conclusion:4C mortality and SOFA scores could be a predictors of mortality in COVID-19 patients in the ICU.